2014
DOI: 10.1186/1755-7682-7-50
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-peptide assay of patients with hyperglycemic emergencies at the Lagos State University Teaching Hospital (LASUTH), Ikeja

Abstract: IntroductionHE are common acute complications of diabetes mellitus (DM) and include diabetic ketoacidosis (DKA), normo-osmolar hyperglycemic state (NHS) and hyperosmolar hyperglycemic state (HHS). They contribute a lot to the mortality and morbidity of DM. The clinical features include dehydration, hyperglycemia, altered mental status and ketosis. The basic mechanism of HE is a reduction in the net effective action of circulating insulin, resulting in hyperglycemia and ketonemia (in DKA) causing osmotic diures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 88 publications
1
5
0
1
Order By: Relevance
“…Measures of serum C-peptide has been widely used as a marker of insulin secretion [40]. The present study revealed that induction of diabetes led to significant decrease in the levels of C- peptide and insulin when compared to control group.…”
Section: Discussionsupporting
confidence: 52%
“…Measures of serum C-peptide has been widely used as a marker of insulin secretion [40]. The present study revealed that induction of diabetes led to significant decrease in the levels of C- peptide and insulin when compared to control group.…”
Section: Discussionsupporting
confidence: 52%
“…It has many specialists’ clinics and runs 24 hours-accident and emergency services and inpatient care services. 10 Although the hospital is a tertiary healthcare facility, it also serves as a primary and secondary healthcare facility; hence, its services are affordable. Consultation and other services are rendered free of charge and only prescribed medicine and laboratory investigations are paid for by the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Measures of serum C-peptide level have been considered as important marker of insulin secretion (Akinlade et al, 2014). Present research study indicated significant (P≤0.01) decrease in serum C-peptide and liver glycogen levels after induction of diabetes.…”
Section: Discussionmentioning
confidence: 47%